Vaccination versus infection with SARS‐CoV‐2: Establishment of a high avidity IgG response versus incomplete avidity maturation. Issue 12 (20th August 2021) - Struck, Friedhelm; Schreiner, Patrick; Staschik, Eva; Wochinz‐Richter, Karin; Schulz, Sarah; Soutschek, Erwin; Motz, Manfred; Bauer, Georg
Abstract: Avidity is defined as the binding strength of immunoglobulin G (IgG) toward its target epitope. Avidity is directly related to affinity, as both processes are determined by the best fit of IgG to epitopes. We confirm and extend data on incomplete avidity maturation of IgG toward severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleoprotein (NP), spike protein‐1 (S1), and its receptor‐binding domain (RBD) in coronavirus disease 2019 (COVID‐19) patients. In SARS‐CoV‐2‐infected individuals, an initial rise in avidity maturation was ending abruptly, leading to IgG of persistently low or intermediate avidity. Incomplete avidity maturation might facilitate secondary SARS‐CoV‐2 infections and thus prevent the establishment of herd immunity. Incomplete avidity maturation after infection with SARS‐CoV‐2 (with only 11.8% of cases showing finally IgG of high avidity, that is, an avidity index > 0.6) was contrasted by regular and rapid establishment of high avidity in SARS‐CoV‐2 naïve individuals after two vaccination steps with the BioNTech messenger RNA (mRNA) Vaccine (78% of cases with high avidity). One vaccination step was not sufficient for induction of complete avidity maturation in vaccinated SARS‐CoV‐2 naïve individuals, as it induced high avidity only in 2.9% of cases within 3 weeks. However, one vaccination step was sufficient to induce high avidity in individuals with previous SARS‐CoV‐2 infection. Highlights: After severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, immunoglobulin G (IgG) toward viral nucleoprotein (NP), receptor‐binding domain (RBD), and spike protein‐1 (S1) shows immature avidity. The breakpoint of avidity maturation correlates with that of IgG production. Patients with more severe clinical symptoms show increased avidity maturation. Two vaccination steps lead to complete avidity maturation. Therefore, vaccination seems to induce protective immunity toward SARS‐CoV‐2 and coronavirus disease 2019 (COVID‐19). Preceding SARS‐CoV‐2 infections enhance avidity maturation after subsequent vaccination. Abstract :